Danske domstole mellem tradition og fornyelse - Gøtze, Michael (Politik, 2010)
The Danish Judiciary was reformed in 1999 as to the important question of appointing new judges. The traditional recruitment of judges in Denmark has predominantly taken place within the cadre of the Danish Ministry of Justice and the explicit purpose of the reform was to alter this tradition and to ensure a broader and more open appointment of judges to the various levels in the court system. However, recent surveys of appointments display a limited movement towards innovation and diversity. The vast majority of new judges are still recruited from within the court system itself or the Ministry of Justice. Although the debate on appointment of judges is controversial in a Danish context, especially among the courts themselves, the article argues that the court system is obliged to implement the reform from 1999 and that the Danish judiciary has an interest in creating diversity among judges and ensuring its independence.